2017
DOI: 10.1088/1751-8121/aa85aa
|View full text |Cite
|
Sign up to set email alerts
|

An alternative route to the system-size expansion

Abstract: The master equation is rarely exactly solvable and hence various means of approximation have been devised. A popular systematic approximation method is the system-size expansion which approximates the master equation by a generalised Fokker-Planck equation. Here we first review the use of the expansion by applying it to a simple chemical system. The example shows that the solution of the generalised Fokker-Planck equation obtained from the expansion is generally not positive definite and hence cannot be interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In this form, the validity and usefulness of the method was demonstrated in many works, e.g. [1,11,12,14,18,20,21,35].…”
Section: Discussionmentioning
confidence: 91%
“…In this form, the validity and usefulness of the method was demonstrated in many works, e.g. [1,11,12,14,18,20,21,35].…”
Section: Discussionmentioning
confidence: 91%
“…Although LNA was historically derived as a second order system size approximation of the chemical master equation, resulting in a Fokker-Planck equation with a stochastic differential equation interpretation and a Gaussian steady state distribution [20], this is not necessary. LNA, as well as higher order approximations, could be derived as Taylor expansions on the moment equations [21]. In fact, it could be shown that LNA could be interpreted as a linear propensity CRN approximation that preserves discreteness and non-negativity of the state variables (see Section V-B).…”
Section: B Linear Noise Approximationmentioning
confidence: 99%
“…Although LNA was historically derived as a second order system size approximation of the chemical master equation, resulting in a Fokker-Planck equation with a stochastic differential equation interpretation and a Gaussian steady state distribution [26], this is not necessary. LNA, as well as higher order approximations, could be derived as Taylor expansions on the moment equations [27]. In fact, it could be shown that LNA could be interpreted as a linear propensity CRN approximation that preserves discreteness and non-negativity of the state variables (see Section V-B).…”
Section: B Linear Noise Approximationmentioning
confidence: 99%